RE-EVALUATION OF ECONOMIC THRESHOLDS USED IN INTEGRATED PEST MANAGEMENT CONSIDERING ACTUAL SOYBEAN SCENARIO. - HAYASHIDA, R. (2022)
Tese (Doutorado) - Universidade Federal do Paraná, Curitiba. Orientador: Prof. Dr. Adeney de Freitas Bueno. Coorientador: Prof. Dr. William Wyatt Hoback.